Peripartum Neurological Injuries and its Outcomes - Muhammad Ali Jamali, Sania, Shazia, Bushra Begum Ramejo, Awais Bashir Larik, Muhammad Munawer Ali Shaikh (Pakistan Journal of Medical & Health Sciences, 2024)
Aim: To study the peri-partum neurological injury and its outcomes. Study Design: Cross sectional study Place and duration of study: Department of Neurosurgery & Department of Obstetrics & Gynaecology, Peoples Medical University Hospital, Nawabshah from 1st July 2022 to 30th June 2023. Methodology: Two hundred and fifty women having a high risk of neurological disorders were included. A high-risk pregnancy was defined with the one having increased threat to fetal morbidity as well as risk of disability presented through clinical symptoms of each case. Biochemical analysis using 5cc blood was conducted for testing positive free beta human-chorionic-gonadotropin in addition to neurological assessment and Doppler ultrasound. A well-designed questionnaire was adapted for extracting information regarding gravidity, parity, gestational hypertension and diabetes, complete clinical history including neurological symptoms, mortality rate mode of delivery and foetal disorders through modifying-ranking-scale of mother. Results: The mean age, gravidity and parity of the study participants was 29.33±1.2, 2.2±1.7 and 2.1±2.0 respectively. Significant number of neurological disorders was observed in before and after pregnancy. Majority of the participants were underwent C-section (62%). Highest ratio of full-term births were reported followed by preterm and abortion. There were 20% those cases who received severe headache post delivery time, on clinical diagnosis out of those 20% cases there were 3% those having subdural hematoma formation. Congenital disorders were observed in only 1 neonate. Obstetric and neurological profile of each patient with each neurological condition was also assessed. Conclusion: The neurological conditions were frequently reported during pregnancy. Seizures, migraine, cerebral venous and intracranial hypertension and sinus thrombosis were reported by majority of the study participants. Keywords: Neurology, Anesthesia, Pregnancy, Neuropathy